2005
DOI: 10.2337/diacare.28.8.1876
|View full text |Cite
|
Sign up to set email alerts
|

Annual Incidence and Clinical Characteristics of Type 2 Diabetes in Children as Detected by Urine Glucose Screening in the Tokyo Metropolitan Area

Abstract: OBJECTIVE—This study investigates the annual incidence and clinical characteristics of type 2 diabetes among school-aged children as detected by urine glucose screening from 1974 to 2002 in the Tokyo metropolitan area. RESEARCH DESIGN AND METHODS— In total, 8,812,356 school children were examined for glucosuria. Morning urine was used for the analysis. When the urine was positive for glucose, an oral glucose tolerance test was carried out to confirm diabetes. RESULTS—In all, 232 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
112
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 35 publications
1
112
3
Order By: Relevance
“…32 Urakami's epidemiological report also mentioned that the increase in the frequency of T2DM in Japanese school children was strongly related to an increasing prevalence of obesity. 31 The discrepancies between our data and this recent report may be attributed to the difference in target populations. All patients in our study required hospitalization for control of high blood glucose and needed intensive treatments, whereas those Japanese T2DM children detected by urine glucose screening in Urakami's recent report demonstrated only slight hyperglycemia.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…32 Urakami's epidemiological report also mentioned that the increase in the frequency of T2DM in Japanese school children was strongly related to an increasing prevalence of obesity. 31 The discrepancies between our data and this recent report may be attributed to the difference in target populations. All patients in our study required hospitalization for control of high blood glucose and needed intensive treatments, whereas those Japanese T2DM children detected by urine glucose screening in Urakami's recent report demonstrated only slight hyperglycemia.…”
Section: Discussioncontrasting
confidence: 99%
“…17 Further, Urakami et al recently reported that the annual incidence of T2DM in school children detected by urine glucose screening was 2.76 / 100,000 from testing done between 1981 and 2002 in the Tokyo metropolitan area. 31 The incidence in Japanese school children is therefore comparable to that in the UK, which is estimated to be 0.21 / 100,000 persons under 16 years old. 32 Urakami's epidemiological report also mentioned that the increase in the frequency of T2DM in Japanese school children was strongly related to an increasing prevalence of obesity.…”
Section: Discussionmentioning
confidence: 92%
“…Most of the studies were conducted in the USA and North European countries, while there were no studies from African or South American countries or from a major part of Asia. Three Japanese [11][12][13], two Austrian [14,15] and two American studies [16,17] were based on the same data source, albeit the data were analysed differently and comprised other study periods. There was a substantial variation in population characteristics and methodological aspects in the identified studies (Table 3), as described below.…”
Section: Resultsmentioning
confidence: 99%
“…The number of children in the populations in which type 2 diabetes was detected ranged from 1,647 [18] to several millions [11][12][13][19][20][21][22][23][24][25] and covered different age categories. The 37 included studies described data about many different ethnicities-Japanese, Taiwanese, multi-ethnic, New Zealand-Maori, New Zealand-European, Turkish, South Asian, Black, Aboriginal, African-American, American Indian, Pima Indian, Ojibwa-Cree, non-Hispanic whites, Hispanic, etc.…”
Section: Study Population and Ethnicitiesmentioning
confidence: 99%
“…BCG immunization rates were provided by The Research Institute of Tuberculosis, JATA. The incidence of type 2 diabetes in all elementary and all junior high school students in Tokyo Japan has been recorded since 1974 [3][4][5] and verified data has been published through 2004 [5]. Data on the incidence of type 2 diabetes was analyzed to determine if the incidence declined after discontinuation of BCG vaccine.…”
mentioning
confidence: 99%